2005
DOI: 10.1021/ja0542688
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Decarboxylative sp−sp3 Coupling

Abstract: A palladium-catalyzed 1,4-enyne synthesis was developed based the decarboxylative coupling of acetylides with allyl electrophiles. Stereochemical studies have implicated palladium-allyl-acetylides as intermediates. Thus, decarboxylative metalation was established as an environmentally benign alternative to transmetalation from alkynyl tin reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
73
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(74 citation statements)
references
References 21 publications
1
73
0
Order By: Relevance
“…Crabtree has recently combined the concepts of oxidative decarboxylative couplings with C À H activation, [13] an approach that was further elaborated by Glorius et al [14] Decarboxylative reaction variants have also been disclosed for Sonogashira couplings, [15] C À S couplings [16] and allylation reactions. [17] Whereas, in principle, carboxylic acids are an appealing source of carbon nucleophiles, synthetic organic chemists may still hesitate to switch from traditional to decarboxylative cross-couplings, reluctant to submit their valuable starting materials to the prolonged thermal stress involved in current protocols, that is, 160 8C over many hours. We saw the efficient heating provided by microwave irradiation as a promising approach to minimize reaction times in decarboxylative cross-couplings and enhance their practicality.…”
Section: Introductionmentioning
confidence: 99%
“…Crabtree has recently combined the concepts of oxidative decarboxylative couplings with C À H activation, [13] an approach that was further elaborated by Glorius et al [14] Decarboxylative reaction variants have also been disclosed for Sonogashira couplings, [15] C À S couplings [16] and allylation reactions. [17] Whereas, in principle, carboxylic acids are an appealing source of carbon nucleophiles, synthetic organic chemists may still hesitate to switch from traditional to decarboxylative cross-couplings, reluctant to submit their valuable starting materials to the prolonged thermal stress involved in current protocols, that is, 160 8C over many hours. We saw the efficient heating provided by microwave irradiation as a promising approach to minimize reaction times in decarboxylative cross-couplings and enhance their practicality.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] vinylarenes, [16] aryl ketones, [17] esters [18] and allyl compounds. [19] The inherent advantage of redox-neutral couplings [14] is that simple carboxylic acid salts replace preformed organometallic reagents as the sources of carbon nucleophiles. [20] However, despite all progress achieved, [21] the requirement for high reaction temperatures remains as their principal drawback.…”
mentioning
confidence: 99%
“…Among the solvents tested, the polar aprotic N-methylpyrrolidone (NMP) was found to be optimal. Using quinoline as the solvent, even higher yields were detected, but the separation of the azomethine product from the basic amine proved to be laborious (entry 19). Similarly, high yields were achieved with NMP after increasing the reaction time to 16 h (entry 22).…”
mentioning
confidence: 99%
“…Related studies were also reported by Studer and Kwong et al [7] Tunge et al reported excellent studies on intramolecular decarboxylative allylations of some activated carboxylate allylic esters. [8] Recently, Tunge et al reported an intramolecular decarboxylative benzylation of b-keto esters, but the benzyl groups participating in this chemistry were limited to benzyls with extend conjugations. [9] To the best of our knowledge, intermolecular decarboxylative benzylation of aliphatic carboxylates has not been explored.…”
Section: Introductionmentioning
confidence: 99%